Un tramway écologique : transformation de la ville et construction des représentations habitantes sur l’environnement à Medellín (Colombie). - Maëlle Lucas (Confins)
The urban project of the Ayacucho tramway in Medellín played a part as disruptive element in the local inhabitants’ environment, and in their perception of it. It made easier the diffusion of a speech valuing a sustainable development and mobilities. In the meantime, the experience of the senses has made obvious the constant rise of the temperature in the valley and the presence of smog. Speeches and storytelling about the city have converged with scientific data to evidence what the sensitive experience confirms about air pollution. The investigation took part in 2017 and 2019, showing the evolution of the representations about the environment, in a context of global diffusion of the « good practices » aiming at limitating the environmental impacts of human activities.